Visible light assisted room-temperature NO2 gas sensor based on hollow SnO2@SnS2 nanostructures - Liu, Di; Tang, Zilong; Zhang, Zhongtai (Sensors and actuators. B, Chemical, 2020)
•The SnO2@SnS2 sensor based on the hollow structure and visible light assistant for highly sensitive detection of ppb-level NO2 at room temperature (25 °C).•The underlying sensing mechanism of the SnO2@SnS2 based NO2 sensor under the visible light irradiation was discussed.•The different effects of humidity on the responses of the SnO2@SnS2 sensor to different concentrations of NO2 were studied and explained. SnS2 is a promising candidate for NO2 sensing applications due to its suitable band gap and large electronegativity. However, SnS2 based gas sensors are still restricted to detect NO2 gas at room temperature due to their giant resistance and poor recovery. Here, we report hollow SnO2@SnS2 nanostructures prepared by a one-step hydrothermal method. The SnO2@SnS2 based sensor showed high response and good recovery to ppb-level NO2 under visible illumination at room temperature (25 °C). The superior sensing performance of the SnO2@SnS2 sensor was attributed to the hollow porous heterojunction structure beneficial for gas diffusion, as well as visible light assistant facilitating charge transfer and gas desorption. This work systematically studied the influence of oxygen concentration in background gas on the NO2 sensing performance of the SnO2@SnS2 sensor, and proposed a physical adsorption model for the NO2 sensing mechanism of the SnO2@SnS2 sensor under visible light at room temperature. In addition, the effect of humidity on the gas sensing performance of the SnO2@SnS2 sensor to different concentrations of NO2 was also discussed.